Lean Six sigmas in academic processes (2020)
The objective of the research was to analyse the influence of the Lean Six Sigma management strategy on the process management of the master in mathematical education of the Universidad Francisco de Paula Santander, San José de Cúcuta, Colombia. The research follows a quantitative approach of field type correlational level. For the analysis and interpretation of the information, tools of diagramming, process mapping, descriptive and multivariate analysis, hierarchical, capacity studies, analysis of measurement systems, design of experiments, error tests and control charts were used. Once the lean six sigma philosophy is implemented, continuous improvement is observed, improvements in process capacity, 99.9% effectiveness in measurement variables, improvement in perceptions of the academic and administrative community, and process standardization, the impact of the application of Lean six sigma in a program is evaluated, demonstrating an efficient flow of its products and processes.